[(PPh3)Ag(CB11H6Y6)] (Y = H, Br): highly active, selective and recyclable Lewis acids for a hetero-Diels-Alder reaction. - Hague, C; Patmore, N; Frost, C; Mahon, M; Weller, A (2001)
The complex [(PPh3)Ag(CB11H6Br6)] 1 is an effective and selective catalyst (0.1 mol% loading) for a hetero-Diels-Alder reaction, which shows a marked dependence on the presence of trace amounts of water, while addition of Ag[Y] [Y = CB11H12, CB11H6Br6, O3SCF3] to a phosphine functionalized support gives an efficient and recyclable Lewis acid catalyst for this transformation.